Lexical indicators of L2 writing performance - Kutay Uzun (Literacy Trek, 2019)
Performance in L2 writing is a complex phenomenon which encompasses complexity, accuracy and fluency. However, relevant literature indicates that lexical performance also plays a role in L2 writing performance as a whole. In this respect, the present study aims to find out which lexical indicators are related to L2 writing performance. Due to the correlational nature of the study, a quantitative research design was preferred. Analyses were performed on a corpus of 160 literary analysis essays written during a compulsorily taken English Literature course by 40 second year students of English Language Teaching at a public university in Turkey. Lexical Complexity Analyzer, which is a reliable software that produces numerical values for lexical performance indicators, was used for the analyses. L2 writing performance scores were assigned to each essay using a 6-point holistic rubric and the essays were re-scored 6 weeks after the first scoring for intrarater reliability. Following the reliability analysis, all variables were tested for the normality of distribution and essay scores were found to be non-normally distributed. Since this variable were to be present in all correlation analyses, Spearman's Rank Order Correlation Coefficient was calculated to see if there was a relationship between essay scores and each of the variables. After the tests of normality, relationships were sought between essay scores and lexical density, lexical sophistication, verb sophistication, number of different words, type/token ratio, lexical variation, verb variation, noun variation, adjective variation, adverb variation and modifier variation. The results showed that L2 writing performance was significantly correlated with lexical sophistication, adjective variation, adverb variation and modifier variation, however, the effect sizes of the significant correlations were too small, so the identified relationships were negligible. On the other hand, significant correlations with small effects were found between L2 writing performance and the number of different words, type / token ratio and verb variation.